2008
DOI: 10.1534/genetics.108.087890
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Fitness Peak Shifts Is Increased at Expanding Range Margins Due to Mutation Surfing

Abstract: Dynamic species' ranges, those that are either invasive or shifting in response to environmental change, are the focus of much recent interest in ecology, evolution, and genetics. Understanding how range expansions can shape evolutionary trajectories requires the consideration of nonneutral variability and genetic architecture, yet the majority of empirical and theoretical work to date has explored patterns of neutral variability. Here we use forward computer simulations of population growth, dispersal, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 56 publications
(72 reference statements)
1
54
0
Order By: Relevance
“…An increasing number of simulation studies are investigating the dynamics and spatial spread of neutral mutations that occur during a period of range expansion (Ibrahim et al, 1996;Austerlitz and Garnier-Géré, 2003;Edmonds et al, 2004;Bialozyt et al, 2006;Klopfstein et al, 2006) but, to date, far less works have considered the fate of non-neutral mutations. It has recently been demonstrated that the surfing phenomenon observed by Edmonds et al (2004) and Klopfstein et al (2006) is likely to lead to the substantially increased survival and spread of deleterious mutants at the front Burton and Travis, 2008), and the results presented here corroborate with those results. Whereas previous works have focussed on using a centroid statistic to describe spread, here we have used spatial extent (as measured by the number of patches occupied) and total population size, in addition to looking at the maximum x-displacement obtained by a surviving mutation.…”
Section: Oj Burton and Jmj Travissupporting
confidence: 90%
See 4 more Smart Citations
“…An increasing number of simulation studies are investigating the dynamics and spatial spread of neutral mutations that occur during a period of range expansion (Ibrahim et al, 1996;Austerlitz and Garnier-Géré, 2003;Edmonds et al, 2004;Bialozyt et al, 2006;Klopfstein et al, 2006) but, to date, far less works have considered the fate of non-neutral mutations. It has recently been demonstrated that the surfing phenomenon observed by Edmonds et al (2004) and Klopfstein et al (2006) is likely to lead to the substantially increased survival and spread of deleterious mutants at the front Burton and Travis, 2008), and the results presented here corroborate with those results. Whereas previous works have focussed on using a centroid statistic to describe spread, here we have used spatial extent (as measured by the number of patches occupied) and total population size, in addition to looking at the maximum x-displacement obtained by a surviving mutation.…”
Section: Oj Burton and Jmj Travissupporting
confidence: 90%
“…Second, with absorbing boundary conditions, the leading edge of the range expansion is most often away from the edge towards the centre of the lattice (Figure 4a), which is due to additional mortality at absorbing edges leading to less rapid population growth. Mutations are most likely to survive when they occur at, or very close to, the leading edge, as it is only then that they and their descendants are most likely to remain at the front and benefit from reduced competition (Klopfstein et al, 2006;Travis et al, 2007;Burton and Travis, 2008). The first of these effects applies equally to mutations regardless of their fitness effect, but the second has a much greater influence on deleterious mutations, as their survival is much more dependent on them surfing the expanding wave front than it is for neutral or beneficial mutations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations